PENGARUH KOMUNIKASI TERAPEUTIK PERAWAT TERHADAP TINGKAT KECEMASAN KELUARGA PASIEN YANG DIRAWAT DI RUANGAN INTENSIVE CARE UNIT - Rajagukguk, Sartika; Dewi Kasih Bratha, Shinta; Hamdani, Hamdani; Darman Putra, Akmal (Ensiklopedia of Journal, 2026)
The anxiety of the patient's family can be reduced by providing good information through therapeutic communication. Skilled therapeutic communication by nurses will make it easier to create a relationship of trust between the patient and family. The purpose of this research was determine the effect of nurses' therapeutic communication on the anxiety level of families of patients treated in the intensive care unit. The sampling technique used a total sampling technique, with a total of 15 respondents. The research design used was Pre-Experiment with a one group pre-test post test design. The data collection tools were a therapeutic communication questionnaire and an anxiety level questionnaire which were analyzed univariately and bivariately using a paired T-test. The results of this research showed that there was an influence of therapeutic communication on the anxiety level of the families of patients treated in the intensive care unit.Keywords: Anxiety; Family;  ICU; Therapeutic Communication